X-ray opaque microgel fiber

JP7629608B2Active Publication Date: 2025-02-14KEIO UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021556164
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-15
Filing Date
2020-11-13
Publication Date
2025-02-14
Estimated Expiration
2040-11-13

AI Technical Summary

Benefits of technology

【0010】 本発明により、可視化可能なマイクロファイバが提供される。当該マイクロファイバは、生体内における留置位置を容易に確認することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629608000001
    Figure 0007629608000001
  • Figure 0007629608000002
    Figure 0007629608000002
  • Figure 0007629608000003
    Figure 0007629608000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing a microfiber that can be visualized. More specifically, a solution of the present invention is a microfiber comprising a hydro gel and containing a radiopaque substance. For example, the microfiber is composed of a core part and a shell part, wherein the shell part contains a radiopaque substance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to microfibers made of hydrogel and containing a radiopaque material. [Background technology]

[0002] Hydrogels are formed from three-dimensional polymer networks containing water, and are highly biocompatible and biodegradable. By microfabricating these, it is possible to create effective tools for delivering cells and drugs into the body, such as microgel fibers. Accurate delivery of drugs to the therapeutic target site is effective not only in increasing the therapeutic effect but also in reducing side effects, and in recent years, various DDS (Drug Delivery System) technologies have been developed. In addition, treatment methods that transplant healthy cells are being developed to treat diseases that develop due to the dysfunction of tissues necessary for maintaining normal biological functions.

[0003] As such cell transplantation therapy, for example, a study on transplanting endothelial cells for liver cirrhosis (Non-Patent Document 1) and a study on transplanting bone marrow mononuclear cells for ischemic heart disease (Non-Patent Document 2) have been reported. In performing such cell therapy, in vitro tissue transplantation, represented by cell sheets, and cell suspension injection are known as cell delivery systems that deliver cells to desired locations in the body. Among them, many studies have been conducted on cell suspension injection therapy, since it can be performed minimally invasively. In the conventional cell suspension injection method, there was a problem that the injected cells were dispersed, making long-term engraftment difficult. To solve this problem, a core-shell type microhydrogel fiber that can be injected by catheter (Non-Patent Document 3 and Patent Document 1) was developed. This core-shell type microhydrogel fiber has excellent mechanical strength, and it is possible to construct three-dimensional structures such as cylinders and tubes. Cell transplantation is possible by encapsulating the cells to be transplanted in the core of the core-shell type microhydrogel fiber and delivering the cells to the transplant site using a catheter or the like. In addition, by encapsulating cells that secrete physiologically active substances in the core, it is possible to release cytokines and the like at the treatment site.

[0004] In this way, core-shell type microhydrogel fibers are effective in cell transplantation therapy, etc. However, because hydrogel fibers have no fixed structure, it is necessary to confirm that they have been delivered to the desired site, but there is no way to visualize the fiber, and in order to ensure the safety of treatment, the development of a way to visualize the fiber is awaited. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2011 / 046105 [Non-patent literature]

[0006] [Non-Patent Document 1] Lee et al., Radiology 278:333-353 2016. [Non-Patent Document 2] Mitsutake et al., Int Heart J 58:435-440 2017. [Non-Patent Document 3] Onoe et al., Nat. Mater. 12:584-590 2013. Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above circumstances, an object of the present invention is to provide a visualized microfiber. [Means for solving the problem]

[0008] In order to solve the above problems, the inventors prepared a core-shell microfiber with a radiopaque substance encapsulated in the shell (Fig. 1, left). When the microfiber was placed in an artery using a catheter, it was confirmed that the shape of the microfiber could be clearly visualized (Fig. 1, right).

[0009] That is, the present invention relates to the following (1) to (4). (1) A microfiber made of hydrogel and containing an X-ray opaque material. (2) The microfiber according to (1) above, characterized in that the microfiber has a shell portion and a core portion. (3) The microfiber according to (2) above, wherein the X-ray opaque material is contained in a shell portion. (4) The microfiber according to any one of (1) to (3) above, characterized in that the X-ray opaque substance is one or more selected from the group consisting of zirconia, tungsten, titanium, iodine, aluminum, copper, tin, gold, palladium and ruthenium. In this specification, the symbol "~" indicates a numerical range including the values ​​on either side of it. Effect of the Invention

[0010] The present invention provides a visualized microfiber, which allows easy confirmation of its placement position in a living body. [Brief description of the drawings]

[0011] [Figure 1] A conceptual diagram of a core-shell type microfiber containing a radiopaque material is shown. The shell of the microfiber shown here is made of alginate hydrogel containing zirconia particles as a radiopaque material, and the core is made of collagen gel containing cells and extracellular matrix (ECM). [Diagram 2] An example of a microfluidic device and a method for fabricating a fiber are shown. [Diagram 3] The results of observation of microfibers containing mouse embryonic fibroblast cells (NIH / 3T3) in the core are shown. "Day 0" is a photograph of the microfiber immediately after preparation, and "Day 5" is a photograph of the microfiber cultured for 5 days after preparation. The diameter of the core and the outer diameter of the shell are shown under each photograph. [Figure 4] Phase contrast micrograph (left) and X-ray contrast image (right) of core-shell microfibers containing zirconia particles in the shell are shown. Microfibers containing 20% ​​(w / w), 30% (w / w), 40% (w / w), or 50% (w / w) zirconia were prepared. [Diagram 5] The graph shows the results of evaluating the visibility (X-ray transmittance) of zirconia-containing microfibers using an aluminum step. The right image shows an image of the zirconia-containing microfiber and the aluminum step (an index of X-ray transmittance) taken with an X-ray imaging device, and the left image shows the relationship between the zirconia concentration and the aluminum equivalent. [Figure 6] This shows the results of X-ray imaging after delivering zirconia-containing microfibers to a rat renal artery using a catheter. The right image shows a schematic diagram of the experiment, and the left image shows an X-ray image. [Figure 7] The X-ray contrast image (right) shows a core-shell microfiber containing tungsten particles in the shell. The microfiber contained 60% (w / w) tungsten. [Figure 8] A phase contrast micrograph (top) and an X-ray contrast image (bottom) of a core-shell microfiber containing titanium powder in the shell are shown. Microfibers containing 38% (w / w) titanium were produced. [Figure 9] The following are phase contrast micrographs of core-shell microfibers, which contain mesenchymal stem cells (MSCs) in the core and zirconia particles in the shell. "Day 1" is a photograph of a microfiber that had been cultured for one day after preparation, and "Day 3" is a photograph of a microfiber that had been cultured for three days after preparation. [Figure 10] The results of measuring the concentration of Vascular Endothelial Growth Factor (VEGF) released from MSCs into the culture medium are shown. The prepared MSCs and zirconia-containing fibers were cultured, and the culture medium was collected every day and replaced with fresh medium. "Day 1" is the VEGF concentration in the culture medium collected on the first day of culture, and "Day 3" is the VEGF concentration in the culture medium collected on the third day of culture. [Figure 11] Confirmation of the effect of the X-ray-opaque microfiber as an alternative to contrast media. The microfiber according to the present invention was inserted into a Y-connector with a hemostasis valve (A), and photographs were taken by moving the microfiber back and forth (B). The branching positions of blood vessels (C) were confirmed by accumulating the photographed images. [Figure 12] A renal failure model (1) created by using a radiopaque microfiber as an embolic material. X-ray angiograms of the kidneys of a model rat are shown. Pre, Post, and Completion respectively show abdominal aortic angiogram before placement of the radiopaque microfiber, plain X-ray photograph after placement of the radiopaque microfiber, and abdominal aortic angiogram after placement of the radiopaque microfiber. [Figure 13] A renal failure model created by using radiopaque microfibers as an embolic material (2). The number of radiopaque microfibers used was adjusted to achieve an embolic area of ​​70% or more or less than 70% in the model rats, and blood urea nitrogen (BUN) and creatinine (Cr) values ​​were measured over time. [Figure 14] A cerebral infarction model created using a radiopaque microfiber as an embolic material (1). An X-ray of the head of a model rat is shown. The arrow indicates the inserted radiopaque microfiber. [Figure 15] A cerebral infarction model created using radiopaque microfibers as an embolic material (2). This is an MRI (T2 weighted) image taken 24 hours after middle cerebral artery embolization in a rat model. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described. An embodiment of the present invention is a microfiber made of a hydrogel, the microfiber containing a radiopaque material. The microfiber according to the embodiment of the present invention is characterized in that it contains a radiopaque substance and can be visualized by X-ray imaging. Whether or not a substance can be used in this embodiment can be evaluated by its mass absorption coefficient. The larger the mass absorption coefficient, the higher the radiopaqueness. For example, suitable radiopaque substances include zirconia containing zirconium (zirconia dioxide, ZrO2), tungsten (W), titanium (Ti), iodine (I), aluminum (Al), copper (Cu), tin (Sn), gold (Au), palladium (Pd), and ruthenium (Ru). Here, the mass absorption coefficients of zirconia, tungsten, and titanium when irradiated with an electron beam of 1 KeV are 4210 cm, respectively. 2 / g, 3683 cm 2 / g, 5869 cm 2 Although not particularly limited, the mass absorption coefficient of the radiopaque material in this embodiment is, for example, 1000 cm when irradiated with an electron beam of 1 KeV. 2 / g or more, preferably 2000 cm 2 / g or more, more preferably 3000 cm 2 For details of the X-ray mass absorption coefficient, see, for example, Kazuo Masato, Journal of the Japan Institute of Metals, Vol. 38 (1974) No. 2.

[0013] The shape of the radiopaque substance contained in the microfiber is not particularly limited as long as the microfiber can be imaged, and examples thereof include particles, powder, flat plates, strings, fibers, porous, and liquid. The size of the radiopaque substance depends on the outer diameter of the microfiber to be produced, and can be easily selected by those skilled in the art. In addition, the size of the radiopaque substance can be easily evaluated by those skilled in the art, and can be measured, for example, under a microscope. The amount of the radiopaque substance contained in the microfiber may be an amount that does not impair the shape or function of the microfiber and is clearly contrasted to a degree that allows visualization, and can be determined by a person skilled in the art by carrying out a preliminary experiment or the like. The appropriate content of the radiopaque substance varies depending on the substance used, but for example, when zirconia particles are used, the content is about 20% (w / w) to 70% (w / w) of the hydrogel constituting the microfiber, preferably about 30% (w / w) to 65% (w / w), and more preferably about 50% (w / w) to 60% (w / w). When the amount of zirconia particles is 20% (w / w) or more, excellent X-ray visibility can be realized, and when the amount is 70% (w / w) or less, excellent strength can be imparted for delivering the microgel fiber into a blood vessel or the like.

[0014] The shape of the microfiber of this embodiment is not particularly limited and can be appropriately selected depending on the application. For example, the microfiber has a fibrous shape, and the cross-sectional shape may be any shape, such as a circle, an ellipse, or a polygon such as a square or a pentagon. The outer diameter may be about 10 μm to 1000 μm for delivery into a blood vessel, for example. The length is also not particularly limited and may be 100 nm to 3000 μm. In the "microfiber made of hydrogel" of this embodiment, the type of hydrogel used as the substrate is not particularly limited, and may be, for example, a hydrogel formed by irradiating a water-soluble polymer such as collagen gel, chitosan gel, gelatin, peptide gel, fibrin gel, alginic acid gel, agarose gel, polyvinyl alcohol, polyethylene oxide, or polyvinylpyrrolidone with ultraviolet light, or a supramolecular hydrogel (see, for example, Dojin News, 118, pp.1-17 2006). The hydrogel of this embodiment may contain an aqueous organic solvent such as ethanol, acetone, ethylene glycol, propylene glycol, glycerin, dimethyl sulfoxide, or a substance that increases the strength of the hydrogel (for example, a crosslinking agent). Furthermore, the microfiber of this embodiment may contain biological substances such as cells, proteins, lipids, sugars, and nucleic acids.

[0015] The microfiber made of the hydrogel according to this embodiment may have a multi-layer structure made of multiple types of hydrogels. Furthermore, the microfiber according to this embodiment may have a structure having a shell part (outer hydrogel) and a core part (inner hydrogel) by providing a layer made of another hydrogel on the outside (hereinafter also described as "core-shell type microfiber of this embodiment"). For example, in the left diagram of FIG. 1, the part "barium alginate gel + zirconia particles" corresponds to the shell part, and the part "cells + collagen" corresponds to the core part. The hydrogels constituting the shell part and the core part may be made of different types of hydrogels, or, in the case of the same type of hydrogel, may be made of hydrogels with different concentrations or strengths. Here, "different strengths" means that the mechanical strengths of the hydrogel constituting the shell part and the hydrogel constituting the core part are different. Examples of the base material for the shell of the hydrogel constituting the core-shell microfiber of this embodiment include, for example, when the core is collagen gel, chitosan gel, gelatin gel, polyvinyl alcohol hydrogel, etc., a gel of a different type or strength from these hydrogels, such as alginate gel, agarose gel, etc. Alternatively, when the shell and core are the same type of hydrogel, such as alginate gel, the alginate concentration may be different between the shell and core.

[0016] When the microfiber of this embodiment is a core-shell type microfiber, the radiopaque substance may be contained in either the core or the shell depending on the purpose of use. When the main purpose is to confirm that the microfiber placed in the living body has been delivered to the desired site, the radiopaque substance may be contained only in the shell, and after the placement position is confirmed, the shell may be removed by the method described below. Alternatively, when cells or the like are contained in the core and placed at a desired position in the living body, and the dynamics of the cells are subsequently traced, the radiopaque substance may be contained in the core.

[0017] The microfiber of this embodiment can be produced using a microfluidic device or the like. For example, in the production of a core-shell type microfiber, a double coaxial microfluidic device (see FIG. 2 or Non-Patent Document 3, etc.) can be used. For example, in the case of producing a microfiber in which the shell part is made of alginate gel and the core part is made of collagen gel containing cells, as shown in FIG. 2, an alginate containing an X-ray opaque substance (e.g., zirconia particles) is injected into 2 (circle 2) and a collagen solution is injected into 1 (circle 1), and then ejected so as to be coaxial as shown in the figure. When an aqueous solution containing a crosslinking agent (e.g., a divalent metal ion such as a calcium salt or a barium salt) for gelling the alginate is injected into 3 (circle 3) and ejected, the alginate is introduced into the aqueous solution containing the crosslinking agent and gelled. The collagen in the core part can be gelled by heating to an appropriate temperature (e.g., about 37°C).

[0018] When producing the microfiber according to this embodiment, the injection speed of a solution for preparing a hydrogel (e.g., an alginate solution, a collagen solution, etc.) may be about 5 μL to 600 μL / min when the aperture of the microfluidic device is about 40 μm to 3 mm, in order to control the shape to a desired shape. The injection speed of a solution for gelation (e.g., an aqueous solution containing a divalent metal ion, etc.) may be about 1 to 10 mL / min, for example.

[0019] After the microfiber according to this embodiment is produced, the hydrogel in the shell or core part can be removed as necessary, leaving only the shell or core part. The hydrogel can be removed, for example, by contacting the hydrogel with a substance that destroys the gel structure. For example, in the case of a hydrogel made of alginate, the hydrogel can be removed by contacting the hydrogel with a chelating agent at an appropriate concentration for removing divalent metal ions, which are crosslinking agents for gelation.

[0020] The microfiber according to this embodiment, particularly the core-shell type microfiber, has excellent strength and can be used to construct three-dimensional structures such as twisted yarn structures, woven fabric structures, helical structures, tube structures, etc. For the preparation method of the three-dimensional structures, see Non-Patent Document 3, etc.

[0021] Purpose 1.Delivery System for Cell Therapy The microgel fiber of this embodiment can be used, for example, as a delivery system for cell therapy. Specifically, cells or the like can be contained in the microfiber (particularly in the core portion) and delivered to the transplantation site by a catheter or the like to perform cell transplantation. In addition, by encapsulating cells that secrete physiologically active substances in the microfiber (particularly in the core portion), cytokines or the like can be released at the treatment site.

[0022] 2. Use as a contrast agent A contrast agent is usually a liquid that contains an X-ray opaque substance. When a contrast agent is injected into a blood vessel and digital subtraction angiography (DSA) is performed, the acquired images can be integrated to obtain an angiographic image. Here, the microfiber of this embodiment can function similarly to a contrast agent by using not only the above-mentioned X-ray photography but also a digital subtraction angiography (DSA) function in combination. Specifically, the microfiber of this embodiment can be moved in a blood vessel by relying on the blood flow like a conventional contrast agent, or can be moved in a blood vessel intentionally. By performing DSA photography in this state, a blood vessel branching image can be obtained like when a contrast agent is used. In most endovascular treatment procedures, the branching of blood vessels is identified and the target blood vessel is cannulated, and a contrast medium is used to identify the branching position of the blood vessel. If the microfiber of this embodiment is used in this procedure, the microfiber is inserted into the blood vessel only during DSA imaging, and can be removed from the blood vessel to the outside of the body immediately after imaging is completed, reducing the amount of contrast medium used and avoiding the physical burden of the contrast medium (risk of contrast-related diseases such as contrast nephropathy and contrast allergy).

[0023] 3. Use as an embolic material The microfiber of the present embodiment can also be used as an embolic substance that blocks blood flow by being placed in a blood vessel. For example, it can be used to create the following disease models. 3-1. Renal failure model By applying an endovascular treatment technique by simply puncturing the tail artery of an experimental animal such as a rat and selectively cannulating the renal artery, it is possible to place the microfiber of this embodiment in the renal artery and create a renal failure model. 3-2. Cerebral infarction model As in the renal failure model described in 3-1 above, a selective middle cerebral artery occlusion cerebral infarction model can be created by puncturing the tail artery of an experimental animal such as a rat, guiding a catheter under X-ray fluoroscopy guidance, and placing the microfiber of this embodiment as an embolic substance within the blood vessel. As described above in 3-1 and 3-2, any organ can be approached if the blood vessel can be cannulated by an intravascular treatment technique or if the blood vessel can be directly reached. Therefore, the microfiber of this embodiment can be used for embolization therapy for various cancers and inflammatory diseases.

[0024] Where this specification is translated into English and contains the singular words "a," "an," and "the," these are intended to include the plural as well as the singular, unless the context clearly indicates otherwise. The following examples are given, but are not intended to limit the scope of the present invention. EXAMPLES

[0025] 1. Method 1-1. Device fabrication The microfluidic device used to fabricate the microfiber is shown in Figure 2. A glass tube with a square cross section and a glass tube with a circular cross section and an inner diameter of about 300 μm at the tip were combined using a connector made with a 3D printer and fixed onto a glass slide with adhesive.

[0026] 1-2. Preparation of NIH / 3T3 cell-containing fibers A 2.5% (w / w) sodium alginate solution was prepared in pure water as a reagent for the shell of the microfiber, and a 100 mM barium chloride solution was prepared as a cross-linking agent to gel the sodium alginate. At that time, sucrose was added to the barium chloride solution to adjust the osmotic pressure to 3% (w / w) of the total. NIH / 3T3 cells were cultured in a 4 mg / mL reconstituted collagen solution at a cell concentration of 1 × 10 8 A solution was used in which the cells were suspended at a concentration of 1.5 μL / mL. Each prepared solution was filled into a syringe and attached to a syringe pump, and the prepared device and each syringe were connected with a Teflon (registered trademark) tube. Each solution was injected into a 145 mM sodium chloride solution to prepare a cell fiber. At this time, the flow rate of the core part was Qcore, the flow rate of the shell part was Qshell, and the flow rate of the crosslinker was Qsheath, with Qcore at 30 μL / min, Qshell at 170 μL / min, and Qsheath at 2000 μL / min. The prepared fiber was cultured in an incubator at 37°C and CO2 5 vol%, and the medium was replaced once every three days.

[0027] 1-3. Preparation of zirconia particle-containing microfibers and tungsten particle-containing microfibers As a reagent for the shell of the microfiber, 2.5% (w / w) sodium alginate solution was added with φ30μm zirconia particles at concentrations of 20% (w / w), 30% (w / w), 40% (w / w), 50% (w / w) and 60% (w / w), or φ1μm tungsten particles at a concentration of 60% (w / w) and stirred using a vortex mixer. As a reagent for the core, 1.5% (w / w) sodium alginate solution was prepared, and as a reagent for the crosslinker, 100 mM barium chloride solution was prepared. Each solution was filled into a syringe and then placed on a syringe pump, and the prepared microfluidic device and each syringe were connected with a tube. In order to prevent the precipitation of the zirconia particles, the zirconia particles contained in the 2.5% sodium alginate solution were stirred with a homogenizer immediately before. The flow rate of the core part was Qcore, the flow rate of the shell part was Qshell, and the flow rate of the crosslinker was Qsheath. The flow rate of the Qcore was fixed at 30 μL / min, the Qshell at 170 μL / min, and the Qsheath at 2000 μL / min to prepare the microfiber. The prepared zirconia-containing microfiber was immersed in phosphate buffered saline, then sucked into a syringe and ejected through a catheter to check whether it could withstand shear force.

[0028] 1-4. Preparation of microfibers containing titanium powder As a reagent for the shell part of the microfiber, 325 mesh titanium powder was added to 2.5% (w / w) sodium alginate solution at a concentration of 38% (w / w) and stirred using a vortex mixer. As a reagent for the core part, 1.5% (w / w) sodium alginate solution was prepared, and as a reagent for the crosslinker, 100 mM barium chloride solution was prepared. Each solution was filled into a syringe and then placed on a syringe pump, and the prepared microfluidic device and each syringe were connected with a tube. In order to prevent the precipitation of titanium powder, the titanium powder contained in the 2.5% (w / w) sodium alginate solution was stirred with a homogenizer immediately before. The flow rate of the core part was Qcore, the flow rate of the shell part was Qshell, and the flow rate of the crosslinker was Qsheath. The flow rates of Qcore, Qshell, and Qsheath were fixed at 15 μL / min, 85 μL / min, and 2000 μL / min, respectively, to prepare the microfiber.

[0029] 1-5. X-ray photography of microfiber The prepared microfibers with zirconia contents of 20% (w / w), 30% (w / w), 40% (w / w), and 50% (w / w), tungsten content of 60% (w / w), and titanium content of 38% (w / w) were transferred to centrifuge tubes or dishes, respectively, and it was confirmed whether they could be imaged using an X-ray imaging device (Artis zee, Siemens Healthineers). Furthermore, the prepared microfiber with zirconia content of 60% (w / w) was delivered to the renal artery of a rat using a catheter, and it was confirmed whether X-ray imaging was possible. The imaging was performed by digital subtraction angiography (DSA). The imaging conditions were tube voltage value of 60 to 70 kV, tube current value of 100 to 200 mA, X-ray exposure time of 2 to 30 s, and number of imaging frames of 15 to 225.

[0030] 1-6. Evaluation of X-ray opacity using aluminum steps The fabricated fiber was placed in a 100 mm diameter dish together with 25 mL of ultrapure water, and an aluminum step (A1050) with a thickness that varied from 2 mm to 16 mm in 2 mm increments was placed next to the dish, and an X-ray fluoroscopic image was obtained. Using image analysis software, the brightness of the acquired image was measured to determine how many mm of aluminum the fiber was equivalent to, and the degree of X-ray opacity was evaluated.

[0031] 1-7. Measurement of Vascular Endothelial Growth Factor (VEGF) released from Mesenchymal Stem Cells (MSC) in Zirconia-containing Fibers 1-7-1. Preparation of MSC and zirconia-containing fibers The reagent used for the shell part of the microfiber was a 2.5% (w / w) sodium alginate solution dissolved in 145 mM sodium chloride solution, to which φ30 μm zirconia particles were added at a concentration of 30% (w / w), and the solution was stirred with a vortex mixer to prepare a 100 mM barium chloride solution as a crosslinking agent to gel the sodium alginate. At this time, sucrose was added to the barium chloride solution to adjust the osmotic pressure to 3% (w / w) of the total. For the core part, human-derived mesenchymal stem cells (MSCs) were added at 4 mg / mL in a reconstituted collagen solution with a cell concentration of 1 × 10 8A solution was used in which the cells were suspended to a concentration of 1.5 μm per mL. Each solution was filled into a syringe and attached to a syringe pump. A device was prepared using a glass tube with a circular cross section and an inner diameter of about 200 μm at the tip, and each syringe was connected with a Teflon (registered trademark) tube. Each solution was injected into a 145 mM sodium chloride solution to prepare a zirconia-containing cell fiber. At this time, the flow rate of the core part was Qcore, the flow rate of the shell part was Qshell, and the flow rate of the crosslinker was Qsheath, with Qcore being 15 μL / min, Qshell being 85 μL / min, and Qsheath being 2000 μL / min. The prepared fiber was immersed in 10 mL of medium and cultured in an incubator at 37°C and CO2 5 vol %, and 1.75 mL of medium was collected every day and 1.75 mL of new medium was added to replace the medium. The collected medium was stored at -30°C until use.

[0032] 1-7-2.Measurement of VEGF concentration released from MSCs into the culture medium The VEGF concentration in the collected medium was measured by ELISA using the Human VEGF Quantikine ELISA Kit (R&D Systems). According to the instruction manual attached to the kit, a microplate containing the measurement sample was prepared, and the measurement was performed using a plate reader (Thermo Scientific Multiskan FC, Thermo Fisher Scientific). First, the plate reader was set up as follows. The absorbance was measured at two wavelengths, 450 nm (main wavelength) and 570 nm (secondary wavelength), and the value was calculated by subtracting the measurement value of the secondary wavelength from the measurement value of the main wavelength. To calculate the concentration using a calibration curve with multiscan FC, the concentration was set in the calibrator wells in the plate layout settings, and the calculation method for creating the calibration curve was set to four-parameter logistic. The microplate was loaded into the prepared plate reader and measurements were performed using the above settings.

[0033] 2. Results 2-1. Cultivation of fibrous cells using barium alginate Figure 3 shows the observation results of the fabricated cell fiber on days 0 and 5. It can be seen that cells were encapsulated in the core on day 0, and that a fibrous tissue had been constructed in the center of the fiber on day 5. These results confirmed that it is possible to culture NIH / 3T3 cells inside barium alginate gel.

[0034] 2-2. X-ray transmission of zirconia-containing microfiber A microscope photograph of the prepared zirconia-containing microfiber is shown on the left in Figure 4. From this result, it was confirmed that the visibility of the microfiber improves when the concentration of zirconia particles is increased. Next, the prepared microfibers with zirconia contents of 20% (w / w), 30% (w / w), 40% (w / w), and 50% (w / w) were placed in centrifuge tubes and X-rayed, and the results are shown on the right in Figure 4. In all cases, the visibility was good in the areas where the fibers overlapped. On the other hand, when focusing on a single fiber that did not overlap, it was confirmed that the fiber was clearly visible through the lens when zirconia particles were added at a rate of 50% (w / w) or more. A microfiber with a zirconia content of 50% (w / w) was evaluated for visibility by X-ray fluoroscopy using an aluminum step. As a result, it was confirmed that it exhibited X-ray opacity equivalent to 3.2 mm aluminum (Figure 5). It was also found that zirconia particles with a particle concentration of approximately 30% (w / w) or more were visible even with X-ray fluoroscopy. Next, the results of X-ray imaging of the fiber delivered to the renal artery of a rat are shown in Figure 6. From this result, it was confirmed that the microfiber containing 60% (w / w) zirconia particles can be localized even in an in vivo environment.

[0035] 2-3. X-ray transmission of tungsten-containing microfiber The X-ray imaging results of the prepared tungsten-containing microfiber are shown in Figure 7. It was confirmed that the microfiber with a tungsten content of 60% (w / w) was clearly imaged, even for individual fibers, as was the case with the microfiber containing zirconia particles.

[0036] 2-4. X-ray transmission of titanium-containing microfiber The X-ray imaging results of the prepared titanium-containing microfiber are shown in Figure 8. It was confirmed that the fiber portion of the microfiber with a titanium content of 38% (w / w) was clearly imaged, similar to the zirconia-containing microfiber and tungsten-containing microfiber.

[0037] 2-5. VEGF concentration released into the culture medium from MSCs and zirconia-containing fibers Phase contrast microscope images of the fabricated MSC and zirconia-containing fiber on Day 1 and Day 3 are shown in Figure 9. It was confirmed that a fiber containing MSCs had been constructed. In addition, VEGF released from MSCs was detected in the medium in which the fiber was cultured, and it was confirmed that its concentration increased over the course of culture time (see Figure 10).

[0038] 2-6. Confirmation of the effectiveness of X-ray opaque microfiber as a substitute for contrast media A microfiber with a zirconia content of 60% (w / w) was inserted into a structure simulating a blood vessel (angioplasty accessory kit, manufactured by Abbott, certification number: 20600BZY01008000) (Figure 11A), and images were taken under DSA by moving the microfiber back and forth in the same way as wire manipulation (Figure 11B). The branching positions of the blood vessels could be confirmed by integrating the images (Figure 11C).

[0039] 2-7. Use of radiopaque microfibers as embolization material 2-7-1. Renal failure model A renal failure model was created by applying an endovascular treatment technique to the rat's tail artery by selectively cannulating the renal artery and placing a microfiber with a zirconia content of 60% (w / w) in the renal artery (Figure 12). It was also confirmed that the embolization area could be adjusted arbitrarily by changing the number of microfibers used when inserting the microfibers under X-ray fluoroscopy. By embolizing both kidneys to an embolization area of ​​70% or more, a "severe model" could be created, and the values ​​of BUN (urea nitrogen) and Cr (creatinine), which reflect renal function, increased significantly. On the other hand, when the embolization area was less than 70%, a "mild model" with mild renal dysfunction was created (Figure 13).

[0040] 2-7-2. Cerebral infarction model As with the renal failure model, a rat's tail artery was punctured, a catheter was introduced under X-ray fluoroscopy guidance, and a microfiber with a zirconia content of 60% (w / w) was placed in the blood vessel as an embolic material to create a rat model of selective middle cerebral artery occlusion and cerebral infarction (Figure 14). Because this material can be placed under X-ray fluoroscopy, it can be placed in the optimal position, making it possible to create a model with a stable infarct area (Figure 15). [Industrial Applicability]

[0041] The microfiber of the present embodiment has excellent visibility, can be placed in a living body and its position can be identified, and allows for safe and secure treatment. Therefore, the present invention is expected to be used in the medical field.

Claims

1. A microfiber made of alginate gel, containing an amount of radiopaque material that allows radiography, and the mass absorption coefficient of the radiopaque material when irradiated with an electron beam of 1 keV is 3000 cm 2 / g or more, the microfiber having a shell portion and a core portion, and a content of the X-ray opaque material being 20% ​​(w / w) or more and 70% (w / w) or less.

2. The microfiber according to claim 1 , wherein the X-ray opaque substance is contained therein in a three-dimensionally dispersed manner.

3. 2. The microfiber of claim 1, wherein the radiopaque material is included in a shell portion.

4. 4. The microfiber according to claim 1, wherein the radiopaque material is one or more selected from the group consisting of zirconia, tungsten, and titanium.

Citation Information

Patent Citations

  • Hydrogel fibers for injection for medical use

    JP2013505791A

  • Multiphasic polymeric particles capable of shape-shifting via environmental stimulation

    US20140147510A1

  • Formulation of solid nano-sized particles in a gel-forming system

    US20140343413A1

  • polymers

    US20150306255A1

  • Injectable hydrogels from microfiber suspensions

    US20160346427A1